Science Learning Cycle Method to Enhance the Conceptual Understanding and the Learning Independence on Physics Learning - Dwi Sulisworo; Novitasari Sutadi (International Journal of Evaluation and Research in Education (IJERE), 2017)
The aim of this study is to observe the application of SLC (science learning cycle) model on improving scientific literacy for secondary vocational schools at physics. Through this research, it will be known its influence of learning methods and contribution to the understanding of physics concepts and student independence learning. This research is a quasi-experimental design with pretest and posttest control group which the independent variable is learning the method and the dependent variable is the conceptual understanding. The result shows that there is an effect of teaching method on the dependent variable. It also shows that the conceptual understanding of the students in the treatment group who applied methods SLC is better than the control group.